ANALISIS TEORITIS PERAN PSIKOLOGI HUKUM DALAM MENGUNGKAP MOTIF PELAKU TINDAK PIDANA DALAM PROSES PERADILAN DI INDONESIA: ANALISIS TEORITIS PERAN PSIKOLOGI HUKUM DALAM MENGUNGKAP MOTIF PELAKU TINDAK PIDANA DALAM PROSES PERADILAN DI INDONESIA - Muhammad Zainal (STIH Zainul Hasan Kraksaan Kraksaan, 2025)
Abstract This study aims to theoretically analyze the role of legal psychology in uncovering the motives of criminal offenders in Indonesia's judicial process. Legal psychology plays a vital role in providing a deeper understanding of offenders' psychological conditions and the factors influencing criminal behavior. Using a qualitative approach and literature review, this research explains how legal psychology tools, such as in-depth interviews and personality tests, can assist judges and investigators in objectively assessing offenders' motives. The findings indicate that the application of legal psychology can enhance the evidentiary process and lead to fairer and more proportional decisions within Indonesia's criminal justice system. Keywords : Legal psychology, perpetrator motive, criminal act, judicial process, Indonesia